Transhepatic permanent pacing in a child with complex cyanotic heart disease after total cavo pulmonary shunt (Kawashima repair) - Anilkumar Singhi; Ejaz Ahmed Sheriff; Kothandam Sivakumar (Indian Pacing and Electrophysiology Journal, 2016)
Complex cyanotic congenital heart diseases with left isomerism are sometimes associated with atrioventricular nodal conduction disturbances that may need permanent pacing. Surgical palliation in such anatomy connecting the superior vena cava to the pulmonary artery precludes a transvenous access for an endocardial pacing lead to the ventricles. Epicardial leads in these patients fail if the pacing thresholds are very high. We report transhepatic permanent ventricular lead implantation for a young boy with heterotaxy complicated by complete heart block.